Experimental Investigation of Amplitude-Modulated Waves for Flame Extinguishing: A Case of Acoustic Environmentally Friendly Technology - Wilk-Jakubowski Jacek (Environmental and Climate Technologies, 2023)
Flame extinguishing methods that are safe for humans and non-invasive to the surrounding environment are being sought worldwide. One of them is acoustic technology, which appears to be an innovative and non-invasive means for flame extinguishing. A highpower and long-range extinguisher was built to explore the possibility of using this environmentally friendly technology. The article includes experimental results, obtained from a laboratory stand, on the possibility of extinguishing flames using amplitude-modulated waves depending on the frequency of the acoustic wave and the distance of the flame source from the extinguisher outlet, which is a scientific novelty. The advantages and disadvantages of acoustic technology are also analysed. The paper concludes that low-frequency acoustic waves are favourable for extinguishing flames because they cause more turbulence in the flame, and thus have a higher extinguishing efficiency. The results are promising and acoustic waves may be used to successfully extinguish flames in a wide range of firefighting scenarios in the future.